Caracterización de las propiedades y fertilidad de los suelos del cantón Marcabelí provincia de El Oro - Castillo Rodriguez, Bayron Eduardo (2015)
The soil as a whole is responsible for plant nutrition as it contains within it the elements they need. They depend directly on the physical and chemical properties of soil that lies in the percentage of fractions of sand, silt and clay that are present in addition to the amount of organic matter, for attachment to the floor so at the Plant roots can take them.Using the tools of GIS knowledge of programs hardware, software and data designed, which can obtain the cartographic cards in digital form from different sites obtained of the canton Marcabelí.The Marcabelí Canton, politically, is located in the province of El Oro-Ecuador; this canton has 148.78 km2 in area, which is approximately 2.61% of the total area of the province, boundaries are: north with Cantons Piñas and Arenillas at; south with Las Lajas.GIS tools are increasingly used in planning processes. Thus, in the formation of a geographic database of the different levels at which the indispensable elements for plants are present can help planning, and improved soil management.Exposed the necessary arguments raised objectives. 1. Develop maps of soil texture, fertility, MO and exchangeable bases. 2. Design a dosing protocol and crops. 3. To characterize the properties and soil fertility in terms of their physical, chemical and physico-chemical properties.Protocols for soil analysis were: for organic matter, Walkley and Black, for mechanical analysis, Bouyucus, for cation exchange capacity, Formaldehyde, for electrical conductivity, the conductometer, for changeable base Na +, Ca ++, Mg ++, K +, macro- and micronutrients N, P, K, Ca, S, B, Fe, Cu, Zn, Mn, atomic absorption spectrophotometer: conductometer. For calculations fertilization recommendations box was used and crop production is considered.The findings indicate that made the source material of the soil that is formed having therein a variety of minerals. The bedrock that led to the sedimentary soils. The source material of soils and climatic factors influenced the presence of sand, silt and clay textural classes. Most tended to soil acidity. Organic matter was poor in the canton. In the low nitrogen predominates. The macro and micronutrients had an irregular and varying concentrations distribution. The cation exchange capacity increased in areas where there was predominance of silt and clay. Maps obtained were: texture, cation exchange capacity, electrical conductivity, organic matter, Na + Ca ++, Mg ++, K + changeable, pH, N, P, K, S, and complementarily B, Fe, Cu, Zn, Mn.